“Restrained eating” vs “dieting”: how are they associated with body weight status, eating behavior and eating frequency among Polish adolescent - Bajerska, Joanna; Pieczyńska, Joanna; Woźniewicz, Małgorzata; Chawłowska, Ewelina; Łagowska, Karolina; Biskupska, Maria (Progress in Nutrition, 2022)
Aim: This study aimed to assess how dieting and dietary restraint were associated with body weight status and eating frequency of certain food groups in a sample of 874 healthy Polish adolescents and young adults aged 16-18 years. Methods: Anthropometric parameters were measured using standardised techniques and instruments. The validated food frequency questionnaire was used to assess habitual dietary intakes. Eating behaviour was assessed with the Three-Factor Eating Questionnaire. The physical activity was assessed by the International Physical Activity Questionnaire. Results: The odds ratio (OR) for overweight and obesity was 1.81 (CI95%:1.22;2.70, p=0.003) times higher among current dieters than nondieters. The odds of being overweight or obese were significantly lower with female sex [OR=0.40 (CI95%:0.27;0.59, p<0.001)]. BMI z-score and WHtR were significantly higher by 0.32 (CI95%:0.18;0.47,p<0.001) and 0.02 (CI95%:0.01;0.02,p<0.001) among dieters than nondieters respectively. Those variables did not differ among restrained and nonrestrained eaters. Dieters were more restrained by 1.71 (CI95%:1.35;2.07,p<0.001) and they had significantly higher disinhibition scores that nondieters did by 0.71 (CI95%:0.33;1.09,p<0.001). Restraint scores were significantly higher by 5.24 (CI95%:4.90;5.57,p<0.001) among restrained eaters vs. unrestrained counterparts. Dieters (especially males) declared less frequent eating of meats & eggs, milk & dairy products, sweets, snacks & fast foods, sweetened beverages. Restrained eaters (especially females) limited the frequency of consumption of most of the unhealthy food items. Conclusions: Effective nutrition education programmes targeted at weight management in adolescents should be gender-specific and concentrate on both the common dietary errors and sensible dietary approaches to weight reduction.